Flow investigation of a miniature pulsatile pump - Ang, Kian Yong (2014)
The overarching goal of this project is to analyse the flow of a miniature pulsatile pump. To ensure reliability and clarity of the study, several experimental variables including types of floating tracer, strength of laser pointer and pump speed were studied. Several parts of the test rig were also modified to reduce leakage and improve quality of laser light sheet generated.